Examining Addiction Levels of Tablet, Phone, and Computer Gaming According to the Parents' Opinions of Students Participating Summer Sports Schools - Albayrak, Veysel; Gacar, Atalay; Nacar, Eyyup; Tutar, Omer Faruk (Lahore Medical Research Center Llp, 2021)
Background: The universe of the research is the athletes of summer sports schools held in Elazig in 2021. The sample consists of the mothers of 669 randomly selected athletes from sports schools. Aim: The aim of the study is to examine the levels of gaming addiction according to the parental opinions of the students participating the 2021 Elazig Summer Sports Schools. Methods: In order to determine the demographic characteristics of the participants in the study, the personal information form(gender, age, school level, mother work status, child's tablet/phone ownership status), and an 18-item scale developed by Ulusoy (2019) was used. Analysis of the data in the research and the calculation of the results found were created through statistical programs in a computer environment. Frequency (f) and percentage (%) distributions of variables were calculated. The data were checked with skewness and kurtosis tests to determine whether they were normally distributed. As a result of these tests and controls, it was determined that the data of the research was parametric. Therefore, t test and variance analysis (Anova) test were used. The error level was taken as p<0.05 in the study. Results: It was determined that there was a statistically significant difference in computer game addiction depending on the gender, mother work status and tablet/phone/computer availability of the students participating summer sports schools in Elazig province. There was no statistically significant difference in computer game addiction depending on educational status and age variables. Conclusion: In line with the study findings, it was observed that the overall average of computer game addiction levels was below average at 45.30 within the framework of the parental opinions of the students participating summer sports schools in Elazig province.
Keywords: Sports; Gaming; Addiction; Technological Device